The development of an intelligent system for the design evaluation and improvement of manufacturability and assembly of product. - Mohd Ripin, Zaidi (Universiti Sains Malaysia, 2005)

(untitled)
Assembly is one of the most important stages of product development. Design for Manufacturing and assembly (DFMA) is one of the approaches to improve the product designs for easier and least assembly cost with high functionality of the products.